Model Tadzkirah Sebagai Model Pendidikan Karakter Islam - Fitri, Anisa; Arisanti, Devi; Indra, Adam Malik; Arnel, Iskandar (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2024)
This article aims to investigate how tadzkirah models in the Islamic perspective character education book by Abdul Majid and Dian Andayani This is an effort so that the education carried out can achieve the desired goal. This type of research is library research using content analysis techniques. The research results first, the Tadzkirah model in this book is a character education model that is present from the derivatives of the theories of Islamic education. These theories are the acronyms of the word tadzkirah which has meaning: i.e. T: show example, A: direct; D: impulse; Z: zakiyah; K: continuity; I: remind; R: repetition; A (O): organize; and H: heart. Second, this Tadzkira model can indeed be used in the implementation of character education, but not all methods in this model are suitable for use by all groups of pupils or all levels of education. Therefore, it is important for educators to be able to understand the character of the students so that they can use appropriate methods. This must be done in the hope of achieving success in character education.